Operating systems a concept-based approach - Dhamdhere, Dhananjay M. (McGraw-Hill, 2009)
Includes definitions and explanations of fundamental concepts in operating systems. This title integrates concepts techniques, and case studies. It offers explanations of concepts, and includes